2017
DOI: 10.1021/acs.joc.7b02855
|View full text |Cite
|
Sign up to set email alerts
|

Base-Controlled Regioselective Functionalization of Chloro-Substituted Quinolines

Abstract: We prepared a number of di- and trifunctionalized quinolines by selective metalation of chloro-substituted quinolines with metal amides followed by reaction with different electrophiles. Metalation of the C-3 position of the quinolinic ring with lithium diisopropylamide at -70 °C is easy to achieve, whereas reaction with lithium-magnesium and lithium-zinc amides affords C-2 or C-8 functionalized derivatives in a regioselective fashion. These complementary methods could be rationalized by DFT calculations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 67 publications
0
15
0
3
Order By: Relevance
“…Whereas 4,7‐dichloroquinoline ( 5 f ) metalation followed by iodolysis allowed the activated position C‐8 to be iodinated in 71 and 68 % yield, the derivative 3‐bromo‐2‐iodoquinoline ( 7 g ) was isolated in 84 and 88 % yield when the 3‐bromo‐substituted quinoline 5 g was employed (Table , entries 5 and 6). Regarding compound 5 f , lithiation with LiTMP in the absence of ZnCl 2 followed by iodolysis afforded a 1 : 1 mixture of iodides at positions C−3 and C−8, which corroborated the importance of pre‐complexation with the zinc salt for reaction regiocontrol. Moreover, it is known that metalation of several electron deficient heterocycles (i. e. diazines) by using lithium amides leads to undesired side reactions due to the high reactivity of the generated organolithium derivatives .…”
Section: Resultsmentioning
confidence: 99%
“…Whereas 4,7‐dichloroquinoline ( 5 f ) metalation followed by iodolysis allowed the activated position C‐8 to be iodinated in 71 and 68 % yield, the derivative 3‐bromo‐2‐iodoquinoline ( 7 g ) was isolated in 84 and 88 % yield when the 3‐bromo‐substituted quinoline 5 g was employed (Table , entries 5 and 6). Regarding compound 5 f , lithiation with LiTMP in the absence of ZnCl 2 followed by iodolysis afforded a 1 : 1 mixture of iodides at positions C−3 and C−8, which corroborated the importance of pre‐complexation with the zinc salt for reaction regiocontrol. Moreover, it is known that metalation of several electron deficient heterocycles (i. e. diazines) by using lithium amides leads to undesired side reactions due to the high reactivity of the generated organolithium derivatives .…”
Section: Resultsmentioning
confidence: 99%
“…Functionalized quinolines are broadly used in agrochemicals [19,20], dyes [21,22], and some biologically active molecules for antimalarial [23][24][25], anticancer [26][27][28][29][30], antiviral [31], antifungal [32], anti-bacterial [33], and anti-inflammatory functions [34,35]. In particular, since the 17th century, the quinoline alkaloid quinine has been viewed historically as the first cure for treating or preventing malaria, [36,37]. Recently, some reports indicated that some quinoline-containing compounds are potentially active SARS-CoV-2 inhibitors [38][39][40], and some quinoline-derived drugs, as shown in Scheme 1, are currently being investigated as a possible cure for COVID-19 infection [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Nesse contexto, dentre os principais grupos dessa classe de reagentes estão os organometálicos de lítio, magnésio e zinco, os quais vêm desempenhando um papel fundamental desde os primórdios da química orgânica sintética (BENISCHKE et al, 2016;MULVEY, 2009;SEYFERTH, 2001 (NISHIMURA et al, 2015;NISHIMURA et al, 2013). Além disso, nosso grupo tem explorado principalmente a metalação de compostos heterocíclicos tais como indolizinas, aril-oxazolinas, tiofenos e quinolinas (Figura 5), visando a obtenção de compostos de interesse, com potencial atividade biológica ou com propriedades fotofísicas, e estudar a influência de grupos dirigentes na regiosseletividade da reação (AMARAL et al, 2014(AMARAL et al, , 2015BATISTA et al, 2015;BOZZINI et al, 2017;DOS SANTOS et al, 2015;MURIE et al, 2018). Nesse contexto, com intuito de prever e racionalizar as reações de metalação, os cálculos computacionais baseados na teoria do funcional de densidade (DFT, do inglês Density Functional Theory) têm desempenhado um importante papel, uma vez que estes possibilitam o cálculo do pKa de hidrogênios presentes nos substratos (BISBALLE et al, 2018;KADIYALA et al, 2013;SNÉGAROFF et al, 2011).…”
Section: Compostos Organometálicos E Suas Aplicaçõesunclassified
“…Adaptado de: (AMARAL et al, 2015;BATISTA et al, 2015;BOZZINI et al, 2017;DOS SANTOS et al, 2015;MURIE et al, 2018) Em resumo, aqui demonstramos a importância de estratégias como a troca halogênio-metal e a metalação na funcionalização de compostos aromáticos e heteroaromáticos, apresentando limitações e vantagens entre os diferentes reagentes 1 Introdução organometálicos. Contudo, outra importante estratégia visando a síntese de compostos biologicamente ativos é a reação de N-arilação, que será explorada adiante.…”
Section: Figura 5 Metalações Regiosseletivas Investigadas Por Nosso unclassified